Starman or Sterrenman: An acquisitional perspective on the social meaning of English in Flanders. (June 2021) - Zenner, Eline; Rosseel, Laura; Speelman, Dirk
Objective: This paper reports on an experiment conducted with 174 Flemish children in three age groups, namely first, third and fifth year of primary school, aiming to assess the social meaning children associate with English-sourced lexemes in Belgian Dutch. Method: The children were presented with 2 versions of a cartoon hero developed specifically for this study: Sterrenman, who only uses Dutch words, and Starman, who uses English alternatives for 17 content words in the cartoon's script. Relying on extensive pretesting, we adapted standard designs and instrumentation from social psychology (the matched guise technique) and language acquisition research to gauge the children's appreciation of the two heroes, their understanding of the English and Dutch vocabulary used in the script, and their level of language awareness. Findings: The key findings are: rather than an incremental increase in favorable social meaning for English from the first to the third age group under scrutiny, we see a decline of the prestige of Dutch in the oldest age group; the children's level of language awareness, receptive vocabulary knowledge and age seem associated with their overall appreciation of Sterrenman and Starman; working with children from various age groups inevitably entails methodological risks. Originality: This is a first and hence exploratory study on the acquisition of the social meaning of English lexemes by EL2 children and their ensuing progressing bilingualism. Implications: Overall, the study helps us contribute to both the recent socio-pragmatic turn in anglicism research and to the upcoming field of developmental sociolinguistics, revealing the transition points in children's acquisition of the social meaning of contact-induced variation and change.